2019
DOI: 10.1002/ijc.32177
|View full text |Cite
|
Sign up to set email alerts
|

Targeted OMA1 therapies for cancer

Abstract: The mitochondrial inner membrane proteins OMA1 and OPA1 belong to the BAX/BAK1‐dependent apoptotic signaling pathway, which can be regulated by tumor protein p53 and the prohibitins PHB and PHB2 in the context of neoplastic disease. For the most part these proteins have been studied separate from each other. Here, I argue that the OMA1 mechanism of action represents the missing link between p53 and cytochrome c release. The mitochondrial fusion protein OPA1 is cleaved by OMA1 in a stress‐dependent manner gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 266 publications
0
37
0
Order By: Relevance
“…Mitochondrial fusion is determined by the tightly regulated L-Opa1/S-Opa1 ratio, where L-Opa1 facilitated mitochondrial inner membrane fusion and S-Opa1 promoted mitochondrial fission. Excessive mitochondrial fission can induce mitochondrion fragmentation, resulting in mitochondrial dysfunction and cell death (62)(63)(64)(65)(66). Under physiological conditions, Oma1 is degraded by sufficient ATP and Yme-1 serves a pivotal role in promoting mitochondrial fusion whilst inhibiting apoptosis by generating L-Opa1.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial fusion is determined by the tightly regulated L-Opa1/S-Opa1 ratio, where L-Opa1 facilitated mitochondrial inner membrane fusion and S-Opa1 promoted mitochondrial fission. Excessive mitochondrial fission can induce mitochondrion fragmentation, resulting in mitochondrial dysfunction and cell death (62)(63)(64)(65)(66). Under physiological conditions, Oma1 is degraded by sufficient ATP and Yme-1 serves a pivotal role in promoting mitochondrial fusion whilst inhibiting apoptosis by generating L-Opa1.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have displayed a significant decrease in the expression of Opa1 along with high mitochondrial fragmentation in hepatocellular carcinoma (118). Tumor suppressor p53 is involved in Oma1-mediated L-Opa1 processing and mitochondrial fragmentation in ovarian and cervical cancer cells (119), the role of which is further supported by the close relationship between S-Opa1 and the p53 signaling pathway (120). Interestingly, in mouse adult fibroblasts (MAFs), Opa1 interacts with mitochondrial F1F0-ATP synthase, favors ATP synthase oligomerization, and finally, protects mitochondria from respiratory chain inhibition by modulating crista shape (89).…”
Section: Mitochondrial Fusion and Fission Shape Cancer Metabolismmentioning
confidence: 99%
“…Interestingly, recent studies revealed another piece of evidence that stress‐activated OMA1 mediates the cleavage of DELE1, which then relays mitochondrial stress to the cytosol (Fessler et al , 2020; Guo et al , 2020). So far, the role of OMA1 in cancer is complicated, depending on the type of cancer, the disease stage, the treatment, and many other factors (Jiang et al , 2014; Alavi, 2019; Amini et al , 2019; Daverey et al , 2019), and the underlying mechanism of OMA1 in regulating tumorigenesis and progression remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%